Histo morphometric evaluation of testes of Black Bengal goats (Bangladesh Veterinarian, 2019)
This study was designed to explore the gross and microscopic structures of the testes of Black Bengal bucks (n = 14) with special emphasis on the seminiferous tubules. A quantitative comparison of the various cell types in the seminiferous tubules of the testes were done. Biometrical values of testes were recorded. The left testes were significantly larger than the right. The mean length, width, weight and circumference of the left testis were 6.7 ± 0.1 cm, 3.9 ± 0.0 cm, 66.9 ± 0.8 gm and 13.4 ± 0.2 cm, respectively. The mean length, width, weight and circumference of the right testis were 6.3 ± 0.0 cm, 3.8 ± 0.0 cm, 66.5 ± 0.8 gm and 13.1 ± 0.1 cm, respectively. For microscopic studies tissue samples were evaluated with quantitative techniques. The testis was encapsulated by tunica toward the mediastinum testis. The testicular parenchyma was divided into convoluted seminiferous tubules and Leydig cells, which were found in the intertubular spaces.The Bangladesh Veterinarian (2018) 35(1&2): 40-46